Fifty key stage musicals - Agnew, Shannon; Schneider, Robert W. (Musical theater director) (Routledge key guides, 2022)
"This volume in the Routledge Key Guides series provides a round-up of the fifty musicals whose creations were seminal in altering the landscape of musical theater discourse in the English-speaking world"--